Coaxial blown spinning cerium modified silicon dioxide nanofiber supported PtGa catalyst, preparation method and application thereof

CN122937787APending Publication Date: 2026-10-20SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610850451.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-12
Publication Date
2026-10-20

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

A PtGa catalyst supported on coaxially blown cerium-modified silica nanofibers, its preparation method, and its application. Porous cerium-modified silica nanofibers obtained by coaxial air-blowing were used as the support. The support has a silica core and an outer core-shell structure containing cerium oxide or cerium silica-oxygen interfacial species. The platinum-gallium active component is loaded on the fiber surface and near-surface region. The catalyst was prepared by preparing a first and second spinning solution, followed by coaxial air-blowing, drying, and calcination to obtain the support, which was then impregnated with platinum and gallium precursors and calcined. Cerium preferentially accumulates in the outer layer of the fiber, enhancing the cerium silica-oxygen and platinum-oxygen-cerium interfacial interaction, improving platinum-gallium particle dispersion and anti-sintering ability, and promoting surface oxygen migration and carbon deposition removal. This catalyst exhibits high activity, selectivity, and stability in the propane dehydrogenation to propylene reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst technology, specifically relating to the field of inorganic nanofiber supports and supported catalysts, and particularly to a coaxial blown cerium-modified silica nanofiber supported PtGa catalyst, its preparation method, and its application in the propane dehydrogenation to propylene reaction. Background Technology

[0002] Fibrous oxide materials, with their high aspect ratio, tunable pore structure, and continuous mass transfer channels, have shown significant application potential in high-temperature catalysis, functional supports, and reactant diffusion and transport. Porous silica nanofibers, possessing high specific surface area, good thermal stability, and ease of loading noble metal active components, are often used as supports for platinum-based or platinum alloy catalysts. Propane dehydrogenation to propylene is an important industrial route for propylene production, and platinum-based catalysts are widely used in this reaction. However, under high-temperature reaction conditions, particle sintering and carbon deposition deactivation easily occur, limiting the long-term stability of the catalysts. To improve the performance of platinum-based catalysts, researchers have attempted to introduce a second metal component, such as gallium, and rare-earth additives, such as cerium. Cerium-modified silica supports can improve the anchoring effect and anti-carbon deposition ability of platinum-gallium clusters by forming a cerium-oxygen-silica interface, introducing oxygen vacancies, and enhancing surface oxygen migration. However, existing methods for preparing fiber catalysts still have significant limitations in controlling the radial distribution of components.

[0003] While traditional electrospinning and single-fluid air-blown spinning can achieve continuous preparation of inorganic nanofibers, they have limitations in terms of complex structure construction and component spatial distribution control. Fibers obtained by conventional single-nozzle spinning are typically solid or uniformly distributed. If elements such as cerium, gallium, and platinum are directly mixed and doped, subsequent influence on element distribution often relies on calcination temperature or treatment atmosphere, resulting in indirect control paths, long experimental cycles, and insufficient structural stability. In cerium-modified silica nanofibers constructed by conventional single-fluid spinning, cerium is usually distributed as an integral dopant throughout the fiber cross-section. Some cerium species are embedded within the fiber, making it difficult for them to fully participate in surface metal anchoring, interfacial electronic regulation, and carbon precursor removal. In other words, although the introduction of cerium theoretically offers advantages in terms of interface and oxygen vacancies, its lack of selective distribution in the fiber radial direction prevents a large number of cerium species from being effectively exposed at the reaction interface, leading to low auxiliary agent utilization efficiency and limiting the improvement in dispersion stability and anti-carbon deposition capabilities of platinum and gallium particles. Therefore, there is an urgent need for a novel fiber catalyst construction method that can take into account efficient preparation, radial structure regulation, and surface cerium enrichment, so that cerium species can be exposed more on the fiber surface or near-surface region while maintaining interfacial interaction with the silica framework, thereby improving the dispersion stability, anti-sintering ability, and propane dehydrogenation reaction stability of the platinum gallium active phase. Summary of the Invention

[0004] Technical Problems Solved: To address the issues of uncontrollable radial distribution of cerium in existing single-fluid spun cerium-modified silica nanofiber carriers, insufficient surface cerium exposure leading to low auxiliary agent utilization efficiency, and the tendency of platinum-gallium active components to migrate, agglomerate, and deactivate due to carbon deposition in high-temperature propane dehydrogenation reactions, this invention provides a coaxial blow-spun cerium-modified silica nanofiber-supported PtGa catalyst, its preparation method, and its application. This catalyst utilizes a core-shell structure carrier with a silica core and a cerium-enriched outer layer constructed by coaxial air-blowing, preferentially enriching cerium species on the fiber surface and near-surface region. Platinum-gallium active components are then loaded onto the cerium-enriched layer through impregnation, enhancing the interfacial interaction between platinum-gallium particles and the carrier, improving sintering resistance and surface oxygen migration capacity, thereby achieving high activity, selectivity, and long-term stability simultaneously in the propane dehydrogenation to propylene reaction.

[0005] Technical Solution: A method for preparing PtGa catalyst supported on coaxial blown cerium-modified silica nanofibers, comprising the following steps: preparing a first spinning solution and a second spinning solution, wherein the first spinning solution contains a silicon source, a template agent, a fiber-forming polymer, and a solvent, for forming a silica core; the second spinning solution contains a cerium precursor, a fiber-forming polymer, and a solvent, for forming a cerium-containing outer layer; feeding the first spinning solution and the second spinning solution into a coaxial blown spinning nozzle respectively, and simultaneously spraying, stretching, refining, and collecting them into composite nanofibers under the stretching action of a high-speed airflow in the outer layer; and processing the obtained... The composite nanofibers were dried and calcined to obtain a porous cerium-modified silica nanofiber support, denoted as C-SiCe-x, where x represents the addition ratio of Ce to Si. Pt and Ga precursors were loaded onto the support, and the catalyst was obtained after drying and calcination. In the first spinning solution, the silicon source was γ-aminopropyltriethoxysilane, the template agents were P123 and CTAB, the fiber-forming polymer was PVP, and the solvent was methanol. In the second spinning solution, the cerium precursor was cerium acetylacetone, the fiber-forming polymer was PVP, and the solvent was methanol.

[0006] The aforementioned coaxial air-blown spinning nozzle has a gas inlet, a first solution inlet, and a second solution inlet. The gas inlet is located on the outer periphery of the second solution inlet, the first solution inlet is located at the center of the nozzle outlet, and the second solution inlet is arranged around the first solution inlet. The nozzle outlet has a concentric circle structure on the front. The gas inlet has a specification of 11G, the first solution inlet has a specification of 21G, and the second solution inlet has a specification of 16G. The propulsion flow rate of the first spinning solution and the second spinning solution is 15 mL / h, and the gas supply pressure is 0.2 MPa.

[0007] In the first spinning solution, the mass ratio of P123, CTAB, PVP, γ-aminopropyltriethoxysilane, and methanol is 0.05:0.05:1.30:1.33:15.84; in the second spinning solution, the mass ratio of cerium acetylacetone, PVP, and methanol is 0.053–0.265:1.30:15.84; wherein, when x is 10, 20, 40, and 50, the mass ratios of cerium acetylacetone, PVP, and methanol are 0.053:1.30:15.84, 0.106:1.30:15.84, 0.212:1.30:15.84, and 0.265:1.30:15.84, respectively. The drying and calcination conditions for the composite nanofibers are as follows: drying at 60℃ for 2 h, then heating to 300℃ at 1℃ / min and holding for 2 h, then heating to 600℃ at 1℃ / min and holding for 2 h.

[0008] The Pt precursor is tetraammineplatinum nitrate, and the Ga precursor is gallium nitrate hydrate. The Pt precursor and Ga precursor are dissolved in deionized water, porous cerium-modified silica nanofiber carrier is added, and the mixture is dried by rotary evaporation at 60°C after stirring. Then, the mixture is heated to 300°C at 5°C / min and calcined for 1 h in air.

[0009] The coaxial blown cerium-modified silica nanofiber supported PtGa catalyst prepared by the above method comprises a porous cerium-modified silica nanofiber support and a PtGa active component loaded on the surface and / or near-surface region of the support; the porous cerium-modified silica nanofiber support has a core-shell structure, wherein the core comprises a silica framework, the outer layer comprises cerium oxide, cerium-containing silicon-oxygen interface species or a combination thereof, and the outer layer contains a Si-O-Ce interface structure.

[0010] The aforementioned PtGa active components include Pt species and Ga species. Pt species include metallic Pt and / or oxidized Pt, and Ga species include Ga oxide and / or Pt-Ga interface species.

[0011] The aforementioned porous cerium-modified silica nanofiber carrier is obtained by coaxial air-blowing spinning and calcination using a first spinning solution and a second spinning solution; the first spinning solution includes P123, CTAB, PVP, γ-aminopropyltriethoxysilane and methanol; the second spinning solution includes a cerium precursor, PVP and methanol; the cerium precursor is cerium acetylacetone.

[0012] The aforementioned porous cerium-modified silica nanofiber carrier is denoted as C-SiCe-x, where x represents the addition ratio of Ce to Si, and x is one of 10, 20, 40 or 50.

[0013] The above-mentioned catalysts are used in the propane dehydrogenation to propylene reaction.

[0014] In the above application, the reaction is carried out in a H2 / Ar mixture at 600°C before the reaction, and the reaction temperature is 550°C. The reaction gases include C3H8 and H2.

[0015] Beneficial Effects: This invention introduces a coaxial structure design into the air-blown spinning system, directly controlling the radial spatial distribution of cerium and silicon during the fiber forming stage. This transforms the conventional bulk doping of cerium species into directional enrichment in the outer layer, significantly improving the availability of cerium at the reaction interface. Compared to bulk-doped cerium-modified silica nanofibers, the cerium in the coaxial core-shell structure carrier is more concentrated on the fiber surface, enabling a more complete formation of the cerium-oxygen-silicon interface, thus providing more anchoring points for the platinum-gallium active component. Experiments show that after platinum-gallium is loaded onto coaxially blown cerium-modified silica fibers, the surface cerium-enriched layer effectively inhibits the high-temperature sintering of platinum-gallium particles. Nitrogen physisorption results show that the specific surface area of ​​the coaxially blown cerium-modified fibers is increased, while retaining abundant micropores and mesopores, ensuring both the thermal stability and mass transfer channels of the silica framework and providing a good dispersion environment for the active component. In the propane dehydrogenation reaction, this catalyst exhibits high initial conversion, maintains a certain level of activity after long-term reaction, maintains propylene selectivity above 98.7%, and demonstrates good stability during long-term operation. Thermogravimetric analysis after the reaction showed that the carbon deposition of the coaxial core-shell structure catalyst was significantly lower than that of the bulk-doped sample. Raman spectroscopy also confirmed that the surface carbon deposition existed in a dispersed state rather than a dense capping layer. These results are attributed to the surface-enriched cerium species promoting oxygen migration through the reversible transition between cerium trivalent and cerium tetravalent phases and oxygen vacancies, which accelerated the dynamic removal of carbon precursors. At the same time, the interfacial interaction formed between platinum gallium and cerium oxide further stabilized the active centers. Thus, the core-shell structure carrier constructed by coaxial blown spinning achieves synergistic cooperation between the silica framework, the surface cerium-enriched layer, and the platinum gallium active phase, enabling the catalyst to exhibit high activity, high selectivity, and excellent anti-sintering and anti-carbon deposition capabilities in the propane dehydrogenation to propylene reaction. Attached Figure Description

[0016] Figure 1 A schematic diagram of coaxial air-blown spinning process, coaxial needle, and coaxial spun fibers.

[0017] Figure 2 Elemental mapping diagram of representative C-SiCe-10 nanofibers.

[0018] Figure 3 XRD patterns of CeO2, SiO2, and C-SiCe-10 nanofibers.

[0019] Figure 4Infrared spectra of CeO2, SiO2, C-SiCe-50, C-SiCe-40, C-SiCe-20 and C-SiCe-10 nanofibers.

[0020] Figure 5 Infrared spectra of CeO2, SiO2, S-SiCe-x series and C-SiCe-x series nanofibers.

[0021] Figure 6 HAADF-STEM images of PtGa / SiO2, PtGa / C-SiCe-10 and PtGa / C-SiCe-50 nanofibers after aging in O2 at 600 °C for 2 h.

[0022] Figure 7 Particle size distribution of PtGa / SiO2, PtGa / C-SiCe-10 and PtGa / C-SiCe-50 nanofibers after aging in O2 at 600 °C for 2 h.

[0023] Figure 8 XPS spectra of O 1s, Si 2p, Ga 2p, Pt 4f, and Ce 3d for PtGa / SiO2, PtGa / S-SiCe-10, and PtGa / C-SiCe-10.

[0024] Figure 9 H2-TPR diagrams of PtGa / SiO2 and PtGa / C-SiCe-10.

[0025] Figure 10 (a) C3H8 conversion and (b) C3H6 selectivity curves of PtGa / C-SiCe-x series nanofiber catalysts as a function of reaction time.

[0026] Figure 11 Stability curves of PtGa / C-SiCe-10 nanofiber catalyst for long-term propane dehydrogenation reaction.

[0027] Figure 12 HAADF-STEM images and elemental mappings of PtGa / C-SiCe-10 after 20 h of reaction.

[0028] Figure 13 TEM image of propane dehydrogenation reaction after 20 h using PtGa / C-SiCe-10 nanofiber catalyst.

[0029] Figure 14 (a) TG and (b) Raman spectra of PtGa / SiO2, PtGa / S-SiCe-10 and PtGa / C-SiCe-10 catalysts after 20 h PDH testing. Detailed Implementation

[0030] The technical solution of the present invention will be further described below with reference to the embodiments and accompanying drawings. The following embodiments are used to illustrate the present invention, but should not be construed as limiting the scope of protection of the present invention. All equivalent substitutions or conventional parameter adjustments made based on the concept of the present invention should fall within the scope of protection of the present invention.

[0031] Example 1: Coaxial air-blown spinning device and nozzle

[0032] The coaxial air-blown spinning device used in this embodiment includes an air supply assembly, a dual-channel liquid supply assembly, a coaxial air-blown spinning nozzle, a receiving assembly, and a heating assembly. The air supply assembly provides a high-speed airflow to the coaxial air-blown spinning nozzle; the dual-channel liquid supply assembly includes two independent solution propellers, which respectively deliver the first spinning solution and the second spinning solution; the receiving assembly is located at the filament exit end of the nozzle and is used to collect the formed fibers; the heating assembly is located between the nozzle and the receiving assembly and is used to promote solvent evaporation and fiber curing.

[0033] The coaxial air-blown spinning nozzle is equipped with a gas inlet, a first solution inlet, and a second solution inlet. Preferably, the gas inlet has a specification of 11G, the first solution inlet has a specification of 21G, and the second solution inlet has a specification of 16G. The nozzle outlet, viewed from the front, has a concentric circular structure, with the smallest circle corresponding to the first solution outlet, the middle annular region corresponding to the second solution outlet, and the outermost annular region being the gas outlet. A high-speed airflow enters from the outer channel, stretching the inner and outer phase solutions at the nozzle outlet, causing the two phase solutions to be simultaneously ejected and refined into composite nanofibers.

[0034] like Figure 1 As shown, this device enables two precursor liquids to form a stable coaxial arrangement at the nozzle outlet, thereby achieving radial partitioning of components during the fiber forming stage. By adjusting the composition of the inner and outer layer solutions, the distance between the nozzle and the receiving component, the liquid supply velocity, and the airflow pressure, structures such as core-shell fibers, spiral fibers, or hollow fibers can be obtained.

[0035] Example 2 Preparation of porous Ce-coated SiO2 nanofiber carrier

[0036] Preparation of the first spinning solution: Weigh 0.05 g P123, 0.05 g CTAB, 1.3 g PVP and 1.41 mL γ-aminopropyltriethoxysilane, add to 20 mL methanol, and stir at room temperature until a uniform transparent sol-gel is formed. This first spinning solution is used to form the SiO2 core.

[0037] Preparation of the second spinning solution: Weigh 0.0053 x g cerium acetylacetone and 1.3 g PVP, add to 20 mL methanol, and stir at room temperature until a uniform, transparent sol-gel is formed, where x can be one of 10, 20, 40, or 50. This second spinning solution is used to form a Ce-containing outer layer.

[0038] The first and second spinning solutions were transferred to 20-50 mL syringes, respectively, and connected to the first and second solution inlets of a coaxial air-blown spinning nozzle. The flow rates of the two solutions were controlled at 15 mL / h, the air supply pressure at 0.2 MPa, the ambient humidity at 30%, and the temperature at room temperature, while the airflow was heated by a heater. The two solutions formed a coaxial liquid flow at the nozzle outlet and were ejected, stretched, and solidified together under the stretching effect of the high-speed airflow to obtain KH550 / Ce precursor / PVP composite nanofibers.

[0039] The obtained composite nanofibers were placed in a crucible and dried in an oven at 60 °C for 2 h. The temperature was then increased to 300 °C at a rate of 1 °C / min and held for 2 h, followed by an increase to 600 °C at a rate of 1 °C / min and held for 2 h. During the calcination process, PVP, KH550, and Ce precursors decomposed or transformed, yielding coaxial air-blown porous Ce-coated SiO2 nanofibers, denoted as C-SiCe-x nanofibers.

[0040] Element mapping results are as follows Figure 3 As shown, C-SiCe-10 nanofibers have a distinct core-shell structure, with Ce mainly concentrated in the outer layer of the fiber and Si mainly distributed inside the fiber, which is consistent with the design of placing the Ce precursor solution in the shell and the Si precursor solution in the core during preparation.

[0041] Example 3 Preparation of PtGa / C-SiCe-x nanofiber catalyst

[0042] The C-SiCe-x nanofibers obtained in Example 2 were ground into a fine powder for later use. 2 mg of tetraammineplatinum nitrate and 1.26 mg of gallium nitrate hydrate were weighed and dissolved in 10 mL of deionized water. The solution was sonicated at room temperature for more than 10 min to fully dissolve the Pt and Ga precursors, thus obtaining a PtGa precursor solution.

[0043] 0.1 g of C-SiCe-x nanofibers were weighed and added to 10 mL of the above PtGa precursor solution. The mixture was stirred at room temperature for 2 h to ensure sufficient contact and adsorption of the Pt and Ga precursors onto the fiber surface and pores. The solution was then dried by rotary evaporation at 60 °C. After drying, the sample was placed in air and calcined at 300 °C with a heating rate of 5 °C / min for 1 h to obtain the PtGa / C-SiCe-x nanofiber catalyst.

[0044] Using the above method, the PtGa active component is preferentially loaded into the Ce-rich outer layer of the fiber and near-surface pores, which is beneficial for constructing PtGa−CeO. x −SiO2 interface structure.

[0045] Example 4: Pore structure and phase characterization of the carrier

[0046] N2 physisorption results showed that enriching Ce on the fiber surface via coaxial air-blowing significantly increased the specific surface area and improved the pore structure of the samples. Specifically, the specific surface area of ​​C-SiCe-20 reached 799.6 m². 2 / g, C-SiCe-10 exhibits a more balanced pore structure in terms of specific surface area, average pore size and micropore volume, which is more conducive to subsequent metal loading and reactant diffusion and transfer.

[0047] Table 1. Average pore size, specific surface area, and micropore volume of porous nanofiber carriers

[0048]

[0049] like Figure 4 As shown, the C-SiCe sample exhibits typical amorphous structure characteristics, and no obvious CeO2 crystalline phase peaks were observed. This indicates that the Ce-related components did not precipitate as a highly crystalline independent CeO2 phase, but may exist in a highly dispersed state or be embedded in the SiO2 network through Si−O−Ce bonding.

[0050] like Figure 5 and Figure 6 As shown, in addition to the Si−O−Si related absorption peak, the C-SiCe-x series samples exhibit a Si−O−Ce related absorption band near 960 cm–1. Moreover, compared with the overall doped samples, the C-SiCe core-shell structure samples show a clearer Ce-related vibrational response, further proving the formation of the Ce-enriched outer layer and the Ce−O−Si interface.

[0051] Example 5: Sintering resistance of PtGa / C-SiCe-x catalyst

[0052] The PtGa / C-SiCe-x nanofiber catalyst prepared in Example 3 was placed in air or O2 atmosphere and heated to 600 °C at a rate of 5 °C / min and held for 2 h for high-temperature aging treatment. Subsequently, the distribution and particle size changes of PtGa particles in the sample were observed using HAADF-STEM.

[0053] like Figure 7 and Figure 8As shown, after oxidative aging at 600 °C for 2 h, the metal particles in the PtGa / SiO2 sample showed significant growth, with an average particle size of approximately 6.01 nm; the particle size in the PtGa / C-SiCe-10 and PtGa / C-SiCe-50 samples was significantly reduced and more concentrated, with average particle sizes of approximately 2.82 nm and 3.23 nm, respectively, indicating that the Ce-enriched outer layer can effectively improve the anti-sintering performance of PtGa particles.

[0054] like Figure 9 As shown, XPS results indicate the existence of a more stable Si−O−Ce interface structure in PtGa / C-SiCe-10, and Ce 4+ With Ce 3+ Coexistence indicates that the surface CeO x It possesses reversible redox capabilities and oxygen vacancies. The Pt 4f and Ga 2p spectra further indicate that the surface CeO₂... x There are electronic interactions between Pt and Pt, which is conducive to the formation of stable Pt−O−Ce interface species and inhibits the formation of large Pt aggregates.

[0055] like Figure 10 As shown, H2-TPR results indicate that the bulk reduction process of PtGa / C-SiCe-10 is concentrated in the 300-400 °C range, suggesting that the surface Ce layer can promote hydrogen overflow and surface oxygen migration, accelerating the reduction of PtO. x and some interface GaO x Low-temperature reduction is beneficial to the formation and stability of the Pt−Ga active interface.

[0056] Example 6 Evaluation of propane dehydrogenation catalytic performance

[0057] The propane dehydrogenation performance of PtGa / C-SiCe-x series nanofiber catalysts was evaluated in a vertical quartz fixed-bed reactor. 40 mg of catalyst was uniformly mixed with 1 g of 50-mesh quartz sand and loaded into a quartz reaction tube with an inner diameter of 9 mm. The sample was fixed at both ends with quartz wool. Before the reaction, reduction was performed in an H2 / Ar mixed gas at a flow rate of 40 mL / min, where H2:Ar = 1:9, at a reduction temperature of 600 °C, and for 1 h. Subsequently, the temperature was lowered to 550 °C for propane dehydrogenation, at a reaction pressure of 1 bar, a reactant gas C3H8:H2 = 2:1, a total flow rate of 40 mL / min, and a propane WHSV of 39 h⁻¹. –1 .

[0058] like Figure 11As shown, the PtGa / C-SiCe-x series catalysts prepared by coaxial air-blown spinning all exhibited good stability during the 600-min test, with the C3H6 selectivity remaining at approximately 98%. Among them, PtGa / C-SiCe-10 showed the best overall performance, with an initial C3H8 conversion of 20.53%, which remained at approximately 19.8% at the end of the reaction, and the C3H6 selectivity remaining stable above 98.7%.

[0059] like Figure 12 As shown, PtGa / C-SiCe-10 maintained good stability during a long-term reaction of 100 h, with the C3H8 conversion decreasing from 20.56% to 16.24% and the C3H6 selectivity slowly decreasing from 98.33% to 96.60%. These results indicate that the Ce-enriched outer layer not only improves the initial dehydrogenation activity of the catalyst but also delays reaction deactivation.

[0060] The HAADF-STEM and elemental mapping results after 20 h of reaction are as follows: Figure 13 As shown, Pt and Ga elements are still dispersed on the fiber surface, and no obvious local enrichment or large bright spots were observed, indicating that the Ce coating layer can provide anchoring points for PtGa species and restrict the migration of active components. Figure 14 The reaction showed that the PtGa / C-SiCe-10 sample still maintained a complete one-dimensional fiber skeleton. The surface carbon was mainly dispersed free or locally grown filamentous and tubular carbon, and no dense covering layer was formed that spread continuously along the fiber surface.

[0061] like Figure 14 As shown, the TG and Raman results after 20 h of reaction further confirm that PtGa / C-SiCe-10 has good anti-carbon deposition ability. Compared with PtGa / S-SiCe-10, PtGa / C-SiCe-10 has significantly reduced carbon deposition while exhibiting higher catalytic activity, indicating that the Ce-enriched outer layer constructed by the coaxial process amplifies the Ce deposition. 3+ / Ce 4+ Its reversible redox properties and oxygen migration capacity help to inhibit coke accumulation and promote the dynamic removal of coke precursors.

[0062] Example 7: Structural differences from single-fluid spinning carriers

[0063] Compared to Ce-doped single-fluid air-blown spinning supports, the C-SiCe-x support in this invention has a more defined "inner Si, outer Ce" core-shell structure. This structure allows more Ce species to be exposed on the fiber surface and directly participate in PtGa particle anchoring, interfacial electronic regulation, and surface oxygen migration processes, while the inner SiO2 framework still provides continuous structural support and mass transfer channels.

[0064] Under the same Ce introduction conditions, the coaxial core-shell structure is more effective than the monolithic doped structure in suppressing high-temperature sintering of PtGa particles, reducing capillary carbon deposition, and improving propane dehydrogenation stability. Therefore, this invention achieves synergistic optimization of the support structure, surface chemistry, and active phase stability.

Claims

1. A method for preparing a PtGa catalyst supported on coaxial blown cerium-modified silica nanofibers, characterized in that, The process includes the following steps: preparing a first spinning solution and a second spinning solution, wherein the first spinning solution contains a silicon source, a template agent, a fiber-forming polymer, and a solvent to form a silica core; and the second spinning solution contains a cerium precursor, a fiber-forming polymer, and a solvent to form a cerium-containing outer layer; feeding the first and second spinning solutions into a coaxial air-blown spinning nozzle, where they are simultaneously sprayed, stretched, refined, and collected into composite nanofibers under the stretching action of a high-speed airflow in the outer layer; and drying and calcining the obtained composite nanofibers to obtain porous cerium nanofibers. The modified silica nanofiber support, denoted as C-SiCe-x, represents the addition ratio of Ce to Si. The catalyst is obtained by loading Pt and Ga precursors onto the support and then drying and calcining them. In the first spinning solution, the silicon source is γ-aminopropyltriethoxysilane, the template agents are P123 and CTAB, the fiber-forming polymer is PVP, and the solvent is methanol. In the second spinning solution, the cerium precursor is cerium acetylacetone, the fiber-forming polymer is PVP, and the solvent is methanol.

2. The preparation method according to claim 1, characterized in that, The coaxial air-blown spinning nozzle has a gas inlet, a first solution inlet, and a second solution inlet. The gas inlet is located on the outer periphery of the second solution inlet, the first solution inlet is located at the center of the nozzle outlet, and the second solution inlet is arranged around the first solution inlet. The front of the nozzle outlet has a concentric circle structure. The gas inlet has a specification of 11G, the first solution inlet has a specification of 21G, and the second solution inlet has a specification of 16G. The propulsion flow rate of the first spinning solution and the second spinning solution is 15 mL / h, and the gas supply pressure is 0.2 MPa.

3. The preparation method according to claim 1, characterized in that, The mass ratio of P123, CTAB, PVP, γ-aminopropyltriethoxysilane, and methanol in the first spinning solution is 0.05:0.05:1.30:1.33:15.84; the mass ratio of cerium acetylacetone, PVP, and methanol in the second spinning solution is 0.053–0.265:1.30:15.84; wherein, when x is 10, 20, 40, and 50, the mass ratios of cerium acetylacetone, PVP, and methanol are 0.053:1.30:15.84, 0.106:1.30:15.84, 0.212:1.30:15.84, and 0.265:1.30:15.84, respectively. The drying and calcination conditions for the composite nanofibers are as follows: drying at 60℃ for 2 h, then heating to 300℃ at 1℃ / min and holding for 2 h, then heating to 600℃ at 1℃ / min and holding for 2 h.

4. The preparation method according to claim 1, characterized in that, The Pt precursor is tetraammineplatinum nitrate, and the Ga precursor is gallium nitrate hydrate. The Pt precursor and Ga precursor are dissolved in deionized water, porous cerium-modified silica nanofiber carrier is added, and the mixture is dried by rotary evaporation at 60°C after stirring. Then, the mixture is heated to 300°C at 5°C / min in air and calcined for 1 h.

5. The coaxial blown cerium-modified silica nanofiber-supported PtGa catalyst prepared by the method according to any one of claims 1 to 4, characterized in that, The catalyst comprises a porous cerium-modified silica nanofiber support and a PtGa active component loaded on the surface and / or near-surface region of the support; the porous cerium-modified silica nanofiber support has a core-shell structure, wherein the core comprises a silica framework, the outer layer comprises cerium oxide, cerium-containing silicon-oxygen interface species or a combination thereof, and the outer layer contains a Si-O-Ce interface structure.

6. The catalyst according to claim 5, characterized in that, The active PtGa component includes Pt species and Ga species, wherein the Pt species include metallic Pt and / or oxidized Pt, and the Ga species include Ga oxide and / or Pt-Ga interface species.

7. The catalyst according to claim 5, characterized in that, The porous cerium-modified silica nanofiber carrier is obtained by coaxial air-blowing spinning and calcination using a first spinning solution and a second spinning solution; the first spinning solution includes P123, CTAB, PVP, γ-aminopropyltriethoxysilane and methanol; the second spinning solution includes a cerium precursor, PVP and methanol; the cerium precursor is cerium acetylacetone.

8. The catalyst according to claim 5, characterized in that, The porous cerium-modified silica nanofiber carrier is denoted as C-SiCe-x, where x represents the addition ratio of Ce to Si, and x is one of 10, 20, 40 or 50.

9. The application of the catalyst according to claim 5 in the propane dehydrogenation to propylene reaction.

10. The application according to claim 9, characterized in that, Before the reaction, the sample was reduced at 600℃ in a H2 / Ar mixture. The reaction temperature was 550℃, and the reaction gases included C3H8 and H2.